A Study on the Utilization of Magnetite for the Recovery of Platinum Group Metals from Chloride Solution - Homchuen, P.; Alorro, Richard; Hiroyoshi, N.; Kijitani, H.; Ito, M. (Taylor & Francis Inc., 2016)
The recovery of platinum group metals (PGMs) from chloride solution using magnetite was investigated. The adsorption of platinum, palladium, and rhodium in chloride medium onto synthetic magnetite powders were studied at different pH conditions, contact time, sodium chloride concentrations, and initial Pt, Rh, and Pd concentrations. Platinum and palladium uptake by magnetite was at a maximum at pH 6–7, and pH 3–4 for rhodium after 24 h with 0.1 mol/dm3 sodium chloride at an initial PGM concentration of 0.05 mol/m3. A sorption mechanism for PGMs was discussed based on the results.